Efeito de subdoses de glyphosate sobre a germinação de sementes das cultivares de soja rr e convecional - Melhoranca Filho, Andre Luiz; Rocha Pereira, Maria Renata [UNESP]; Martins, Dagoberto [UNESP] (Universidade Federal de Uberlândia (UFU), 2011)
The aim of this work was to evaluate the quality of seeds of two soybean cultivars CD-216 and CD-212RR, under subdoses of glyphosate (1,3; 2,6; 5,3 and 11,5 g e.a.ha(-1)). The experiments carried out in Laboratory Fisiologoa Plant in the Uniderp, city of Dourados/MS. The experimental design used was in blocks entirely at random, with four repetitions. After soaking, evaluated the following parameters eight days after imbibition: % germination, seedling dry weight, length of root and shoot. Seeds of both cultivars (CD-212RR and CD216) reduce the percentage of germination, with the increasing of glyphosate concentration in soaling, and CD-216 was more sensible to herbicide.

O objetivo deste estudo foi avaliar a qualidade de sementes das duas cultivares de soja (CD-216 e CD-212RR), submetidas à subdoses de glyphosate (1,3; 2,6; 5,3 e 11,5 g e. a. ha-1). O experimento foi conduzido no Laboratório de Fisiologoa Vegetal da Uniderp, município de Dourados/MS, inteiramente casualizado, com quatro repetições. As sementes foram embebidas nas diferentes subdoses de glyphosate por quarenta minutos. Após a embebição, avaliaram-se os seguintes parâmetros oito dias após embebição: % germinação, massa seca de plântula, comprimento de radícula e parte aérea. Sementes de ambas cultivares (CD-212RR e CD-216) reduzem o percentual de germinação, com o aumento da concentração de glyphosate na embebição, sendo a cultivar CD-216 mais sensível ao herbicida.
Effect of subdoses glyphosate on the germination of seeds of soybean cultivars rr and conventional
Keywords: Glycine max; Glyphosate; Herbicide; Transgenic